Effects of Strain Rate on the TRIP–TWIP Transition of an Austenitic Fe-18Mn-2Si-2Al Steel - Raposo, Marcio Daniel (2019)
A fully austenitic Fe-18Mn-2Si-2Al transformation-induced plasticity (TRIP) steel was tensile tested from quasi-static to low-dynamic regime at three different strain rates: 4.7 × 10−4, 1.3 × 10−1, and 8.3 × 100 s−1. Typical two-stage transformation mechanism, TRIP γ → ε → α′, was observed for samples tested at 4.7 × 10−4 s−1. At higher strain rates, the increase in temperature due to adiabatic plastic work shifts the stacking fault energy (SFE) towards a twinning-induced plasticity–SFE-range modifying the mechanical behavior of the alloy. This change on the deformation mechanism leads to a lower work hardening capacity and a higher elongation to rupture in samples tested at 1.3 × 10−1 and 8.3 × 100 s−1. In this context, the alloy maintains its energy absorption capability with a maximum reduction of 3.6 pct according to the Rm × A parameter. The Md temperature, experimentally determined in the present study, proved to be a useful tool for understanding the material’s behavior.